2015
DOI: 10.1093/mnras/stv2706
|View full text |Cite
|
Sign up to set email alerts
|

The abundance and colours of galaxies in high-redshift clusters in the cold dark matter cosmology

Abstract: High redshift galaxy clusters allow us to examine galaxy formation in extreme environments.Here we compile data for 15 z > 1 galaxy clusters to test the predictions from a state-of-theart semi-analytical model of galaxy formation. The model gives a good match to the slope and zero-point of the cluster red sequence. The model is able to match the cluster galaxy luminosity function at faint and bright magnitudes, but under-estimates the number of galaxies around the break in the cluster luminosity function. We f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 123 publications
(184 reference statements)
2
8
0
Order By: Relevance
“…On a related note, Licitra et al (2016) have shown that clusters at z < 1 in SAMs suffer from ETG populations with too low an abundance and too blue colors, while ∼10% of model clusters have positive RS slopes. On the other hand, Merson et al (2016) found broad consistency between observations and SAMs in the zeropoint and slope of the RS in z > 1 clusters. This suggests that errors creep into the evolution of cluster galaxies in SAMs at z < 1.…”
Section: Shortcomings Of Galaxy Formation Modelssupporting
confidence: 55%
“…On a related note, Licitra et al (2016) have shown that clusters at z < 1 in SAMs suffer from ETG populations with too low an abundance and too blue colors, while ∼10% of model clusters have positive RS slopes. On the other hand, Merson et al (2016) found broad consistency between observations and SAMs in the zeropoint and slope of the RS in z > 1 clusters. This suggests that errors creep into the evolution of cluster galaxies in SAMs at z < 1.…”
Section: Shortcomings Of Galaxy Formation Modelssupporting
confidence: 55%
“…The GP14 model was calibrated on the MS-W7 simulation (Guo et al 2013;Lacey et al 2016a), which adopts the same WMAP7 cosmology as the simulations used in this work but has a much larger volume (500h −1 M pc) 3 and a lower mass resolution of 9.35 × 10 8 h −1 M⊙. The GP14 model successfully reproduces a wide range of observations (Gonzalez-Perez et al 2014;Lagos et al 2015;Merson et al 2016).…”
Section: Model Galaxiesmentioning
confidence: 87%
“…Ascaso et al 2008;Mei et al 2009;Ascaso et al 2014b) in agreement with Merson et al (2015). PhotReal overcomes this problem by re-computing the photometry and therefore, shifting some galaxies from the red sequence to the blue cloud.…”
Section: Color-magnitude Relationmentioning
confidence: 97%